A case of dysferlinopathy (Miyoshi distal myopathy limb-girdle muscular dystrophy type 2b phenotype) from a tertiary care hospital - Sivasamy, Manoj; R., Shreenidhi; M. K., Nishaanth; M., Jagadeesan; S., Prasanna Karthik; Fernandez, Kevin (International Journal of Advances in Medicine, 2023)
Limb girdle muscular dystrophy type 2B (LGMD2B) and Miyoshi myopathy are caused by similar mutations in the dysferlin gene. The phenotype of these allelic disease variants can vary considerably. We report a young male with severe and rapidly progressing muscle disorder with increased creatine phosphokinase (CPK) and confirmatory muscle biopsy findings. Genetic testing was done. A homozygous nonsense variation in exon 23 of the DYSF gene, which was consistent with the patient’s clinical reports of dysferlinopathy. Clinical phenomenology and preferential muscle involvement lead one to the gold standard genetic testing in heritable myopathies, which was well established in this report.